STRATEGI PENGEMBANGAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN EFEKTIVITAS KERJA KARYAWAN PADA CV. KORI DEWATA KARYA TABANAN - Ni Putu Ayu Daniswari; I Nengah Aristana (Universitas Triatma Mulya, 2023)
In general, the effectiveness of employees' work can be increased through several strategies. There are several strategies in increasing the effectiveness of employee work used as follows: HR recruitment strategy CV. Kori Dewata Karya is in accordance with the required field, a workforce placement strategy in accordance with the skills and abilities of the employees, performance improvement by developing employee potential through the training process. This study aims to determine and analyze the Human Resource Management Development Strategy in Improving Employee Work Effectiveness at CV. Kori Dewata Karya. The type of research used is descriptive qualitative. Data collection techniques using observation techniques, interviews, and literature study. Based on the results of interviews that have been analyzed using the SWOT analysis method so that it can be described the Human Resource Management Development Strategy used by CV. Kori Dewata Karya. SWOT analysis is the identification of various factors systematically to formulate corporate strategy. From the results of the analysis obtained a growth strategy or growth oriented strategy, this strategy indicates a strong company condition and is able to continue to grow by taking the opportunities and opportunities that exist to achieve maximum goals. The results of the SWOT analysis are illustrated using a SWOT analysis diagram showing the HR Management Development Strategy is in quadrant I, where the total weighted score for strengths and weaknesses is 2.94 while the total weighted score for opportunities and threats is 2.70. In this position CV. Kori Dewata Karya has strengths and opportunities so the strategy that must be applied is to support aggressive growth or optimize progressive opportunities.